Monetary policy delegation and transparency of policy targets: A positive analysis - Kai Hielscher (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2011)
We show that, in a two-stage model of monetary policy with stochastic policy targets and asymmetric information, the transparency regime chosen by the central bank does never coincide with the regime preferred by society. Independent of society's endogenous choice of delegation, the central bank reveals its inflation target and conceals its output target. In contrast, society would prefer either transparency or opacity of both targets. As a conclusion, the choice of the transparency regime should be part of the optimal delegation solution.
urn:nbn:de:gbv:705-opus-29369
Keywords: E52; E58; 330; central banking; monetary policy; communication; delegation; positive analysis